"Behind" the text : history and biblical interpretation - Bartholomew, Craig G., 1961-; Scripture and Hermeneutics Seminar (2002 : Boston, Mass.) (Carlisle, Cumbria : Paternoster Press ; Grand Rapids, Mich. : Zondervan, 2003)
Publisher's description: This volume well illustrates the Christian adage of faith pushes reason to achieve goals previously unsuspected but still proper to itself. The last few centuries have seen the development of an epistemology and an understanding of history that never leave the closed system thinking of both Modernism and Post-Modernism. In biblical studies their child is the Historical Critical Method. The essays presented here respect the need and fruitfulness of a critical historiography while beginning the much-needed process of correcting the philosophical tenets underlying much modern and postmodern biblical research. The result is a book that mediates a faith understanding, both theoretical and practical, of how to read the Bible authentically as a Christian today.
Rethinking history. 11. Knowing and believing : faith in the past / Iain Provan -- 12. Creation and promise : towards a theology of history / Murray A. Rae -- Tradition and history. 13. The conflict of tradition and history / Walter Sundberg -- 14. Tradition, biblical interpretation and historical truth / C. Stephen Evans -- History and narrative. 15. Ricour on history, fiction, and biblical hermeneutics / Gregory J. Laughery -- 16. (Pre) figuration : masterplot and meaning in biblical history / David Lyle Jeffrey -- History and biblical interpretation. 17. Reconstructing and interpreting Amos's literary prehistory: a dialogue with redaction criticism / Karl Möller -- 18. What lesson will history teach? The book of the twelve as history / Christopher Seitz -- 19. Divine speaking as godly action in Old Testament narrative: the metaphysics of Exodus 14 / Neil B. MacDonald -- 20. Inhabiting the story: the use of the Bible in the interpretation of history / Stephen I. Wright.
Based on papers of the consultation of the Scripture and Hermeneutics Seminar, held in Boston, 2002.
Includes bibliographical references (p. 518-519) and indexes.
Keywords: Bible -- Historiography -- Congresses; Bible -- Hermeneutics -- Congresses